PENGARUH PERSEPSI TERHADAP PRIVATE LABEL BRANDS PADA PERUSAHAAN RITEL CARREFOUR DI KOTA SOLO - Retno - Susanti; Suprihatmi Sri Wardiningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT This research aimed to analyze the influence of consumer perceptions, price perception and perceived risk to private label brands in the retail company Carrefour in Solo. After a review of the previous literature and research, hypothesis are made that consumer perception, price perception and perceived risk influence to private label product brands significantly, and price perception variable is a dominant variable affecting of private label brands product. Primary data obtained from questionnaires to 100 respondents using purposive sampling techniques, and performed analyzes with SPSS. Analysis multiple linear regression, F-test, t-test, and the coefficient determination, with the result: Consumer Perceptions (X1), Price Perception (X2), and the Perceived Risk (X3) significantly influencing to private label brands, and price perception variable is a dominant variable on the success of private label brands. It means the data obtained supports the hypothesis. Research found that the quality of the product is perceived by consumers, they believe that private label brands with low prices image have quality that is comparable to the national brands, consumers are not ashamed and do not have to bear the risk of purchasing the products. These all are the factors that are proven to be the perception in purchasing private label products brands. Keywords: Consumer Perceptions, Price Perception, Perceived Risk, and Private Label Brand.